The unseen realm : recovering the supernatural worldview of the Bible - Heiser, Michael S. (Lexham Press, 2015)
The psalmist declared that God presides over an assembly of divine beings (Psa. 82:1). Who are they? What does it mean when those beings participate in God's decisions (1 Kings 22:19-23)? Why wasn't Eve surprised when the serpent spoke to her? Why are Yahweh and his Angel fused together in Jacob's prayer (Gen. 48:15-16)? How did descendants of the Nephilim (Gen. 6:4) survive the flood (Num. 13:33)? What are we to make of Peter and Jude's belief in imprisoned spirits (2 Pet. 2:4; Jude 6)? Why does Paul describe evil spirits in terms of geographical rulership (thrones, principalities, rulers, authorities)? Who are the "glorious ones" that even angels dare not rebuke (2 Pet. 2:10-11)? Dr. Michael Heiser explores these biblical questions in The Unseen Realm: Recovering the Supernatural Worldview of the Bible. The Unseen Realm presents the fruit of Dr. Heiser's fifteen years of research into what the Bible really says about the unseen world of the supernatural. His goal is to help readers view the biblical text unfiltered by tradition or by theological presuppositions. He presents a clear biblical theology that cuts through our modern worldview that tends to ignore the unseen world. "People shouldn't be protected from the Bible," Dr. Heiser says. But theological systems often do just that, by "explaining away" difficult or troublesome passages of Scripture because their literal meaning doesn't fit into our tidy systems. In The Unseen Realm, Michael Heiser shines a light on the supernatural world--not a new light, but rather the same light the original, ancient readers--and writers--of Scripture would have seen it in, given their historical and cultural milieu. This light allows today's pastors and scholars to understand the biblical authors' supernatural worldview by presenting a biblical theology that embraces, rather than avoids, the unseen realm. Take your study even further with The Unseen Realm: A Question & Answer Companion. --